Epigenetic Alterations and Prenatal Maternal Depression. Issue 12 (17th July 2017) - Nemoda, Zsofia; Szyf, Moshe
Abstract : Major depressive disorder of the mother affects 6 to 17% of pregnancies worldwide and can lead to negative outcomes, such as preterm delivery and later mental health problems of the child. It has been proposed that developmental programming has long‐lasting effects in the offspring that might be mediated by epigenetic mechanisms, such as DNA methylation. Altered stress regulation or impaired immunological function of the mother can potentially affect DNA methylation processes of the fetus, changing gene expression levels in utero. These underlying biological processes can be tested in animal models, where pharmacological experiments using epigenetic drugs can prove causality. Recent human studies show that DNA methylation changes of hypothesis‐driven candidate gene regions, such as the promoter of the glucocorticoid receptor and the serotonin transporter, were associated with maternal depression in peripheral tissue samples of newborns' cord blood, infants' saliva, or adults' peripheral blood. In addition, epigenome‐wide association studies using blood cells show modest but significant changes in a subset of genes involved in immune functions. These DNA methylation changes were found mainly in enhancers, which point to regulatory effects in gene expression. Limited number of studies using brain tissue showed a significant overlap of differentially methylated genes in the different studies. In conclusion, prenatal maternal depression can induce covalent modifications in the offspring's DNA, which are detectable at birth in leukocytes and could be potentially present in other tissues, consistent with the hypothesis that system‐wide epigenetic changes are involved in life‐long responses to the psychosocial environment in utero. Birth Defects Research 109:888–897, 2017. © 2017 Wiley Periodicals, Inc.